Soy production as a vector for sustainability: an econometric approach for Mato Grosso (Research, Society and Development, 2021)
One of the obstacles to achieving sustainable development is to formulate measurement mechanisms, such as sustainability indicators, which are key tools for monitoring and assessing progress towards sustainable development. The aim of this article is to analyze how soybean production influences the sustainability of municipalities in the State of Mato Grosso, through the construction of an ISPS Soybean Production Sustainability Index in 2010. The results showed that the social dimension was the one that most explained the total variability of the data. In relation to the individual impacts of the indicators, it was found that the harvested area is the one that most influences the variability of ISPS, followed by the Recovery Plan for Degraded areas and vulnerable to poverty. In this study, it is concluded through the proposed Soybean Production Sustainability Index, that soybean production contributes to the sustainability of the municipalities of the State of Mato Grosso, once the municipalities with higher soybean production such as Sorriso, Lucas do Rio Verde, Campo Novo do Parecis have a high level of sustainability.